Hands-On High Performance with Spring 5 : Techniques for Scaling and Optimizing Spring and Spring Boot Applications. - Mehta, Chintan (Packt Publishing Ltd, 2018)
Spring 5.0 brings major advancements in the rich APIs provided by the Spring framework and thus creates a need for developers to master its tools and techniques to achieve high-performing applications. This book will help you improve the speed of your code and optimize the performance of your apps.